THE EFFECTS OF DIETS CONTAINING DIFFERENT LEVEL OF NON-STARCH POLYSACCHARIDES ON PERFORMANCE AND CANNIBALISM IN LAYING HENS - Hartini, S.; Choct, M. (Journal of the Indonesian Tropical Animal Agriculture, 2010)
An experiment was conducted to observe the effect of different diets containing different level ofnon-starch polysaccharides (NSP) on performance and cannibalism of laying hens. Six diets (wheatbased,rice hull-based, plant protein-based, millrun-based, MOS, and bentonite) were used and wererandomly given to 6 groups of ISA Brown hens, with 18 replicates per group and 5 birds per replicatefor 8 weeks. The results showed that diets did not have a significant effect (P>0.05) on cannibalismmortality, but numerically the rice hull diet gave the lowest effect, the millrun gave the intermediateeffect, whereas the plant protein diet gave the largest negative effect. Diet significantly affected feedintake (P<0.01), egg production (P<0.01), feed to egg ratio (P<0.01) and egg weight (P<0.05). Birds onmillrun diet had the lowest intake, but the feed to egg ratio was superior and egg production was thehighest compared to those fed other diets. In contrast, the feed to egg ratio in rice hull diet was inferior,and egg weight was also lighter than those fed other diets. In conclusion, fibre sources have beenverified as contributing factors involved in the outbreak of cannibalism in laying hens. Diets containinghigh insoluble NSP had a potential to decrease the mortality due to cannibalism.